Analisis Faktor-Faktor Yang Memengaruhi Kelemahan Sistem Pengendalian Internal Pemerintah Provinsi Di Sumatera Tahun 2017-2021 (Jurnal Kendali Akuntansi, 2024)
There are still many problems with regional autonomy, one of which is fraud and increasing cases of corruption. Fraud in organizations, whether public or private, is usually caused by weak government internal control systems. This research aims to analyze the factors that influence the weaknesses of the provincial government's internal control system in Sumatra in 2017-2021. The type and data used in this research is a quantitative method with secondary data. The results of this research state that the variables Special Allocation Funds, Government Complexity, Original Regional Income, and Capital Expenditures have a significant positive effect on the Weaknesses of the Provincial Government's Internal Control System in Sumatra in 2017-2021. Meanwhile, the Government Size variable has a significant negative effect on the Weaknesses of the Provincial Government's Internal Control System in Sumatra in 2017-2021.